Genomic and Phenotypic Variations Among Thai-53 and Mycobacterium leprae Clinical Isolates: Implications for Leprosy Pathogenesis and Research - Tiago Araujo Gomes; Tatiana Pereira da Silva; Edson Machado; Sidra Ezidio Gonçalves Vasconcelos; Bruno Siqueira Mietto; Daniela Ferreira de Faria Bertoluci; Patricia Sammarco Rosa; Roberta Olmo Pinheiro; Philip Noel Suffys; Letícia Miranda Santos Lery; Flavio Alves Lara (Pathogens)
Throughout Mycobacterium leprae’s (M. leprae) evolutionary trajectory, nearly half of its genome was converted into pseudogenes. Despite this drastic reduction in genetic content, the genome sequence identity among M. leprae isolates worldwide is remarkably high compared to other pathogens. In this study, we investigated the genotype and morphotype of three M. leprae strains: the reference strain Thai-53 (genotype 1A), and two clinical isolates from Brazilian leprosy relapse patients, which were Br014-03 (genotypes 3I) and Br014-01(4N). We compared their genome sequences and their interaction with human Schwann cells from the ST88-14 lineage and with human primary macrophages. On the genetic level, we observed over a hundred missense mutations in the three strains, translated into significant phenotypic changes such as: prolonged doubling time, altered cytokine induction, reduced interaction rates, and decreased intracellular viability in Schwann cells. Our findings underscore the concept that despite their 99.992% identity, even small genomic disparities in M. leprae genomes can elicit substantial alterations in bacilli interaction with host cells and subsequent immune responses. Consequently, our data could lead to better comprehension of correlation between pathogen mutations and the diverse clinical manifestations observed in leprosy patients.